Effectiveness of Integration of Moving Bed Biofilm Reactor and Activated Carbon in Treating Wastewater from Health Center - Mahmud, Inayah; Budirman, Budirman; Sahani, Wahyuni; Khaer, Ain (Buletin Penelitian Kesehatan, 2026)
Background: The integration of MBBR and activated carbon merges effective biological degradation with superior adsorption capabilities, enhancing pollutant removal while addressing the limitations of each technology individually. This hybrid system is ideal for small facilities, offering comprehensive, cost-effective wastewater treatment with a flexible design and low operational costs. This study aims to evaluate the effectiveness of hybrid Moving Bed Biofilm Reactor (MBBR) and activated carbon technology for wastewater treatment of health centers in Makassar City. Methods: The research was conducted experimentally using three variations of contact time (2, 4, and 6 hours), and the physical and chemical parameters measured, namely Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), ammonia (NH₃), temperature, and pH, were measured before and after treatment. The data were analyzed using the Kruskal-Wallis statistical test to test differences between treatments and the Wilcoxon Signed-Rank Test to evaluate the significance of differences before and after treatment. Results: The results showed that this hybrid system reduced BOD by 80.41%, COD by 81.40%, and NH₃ by 79.38%, with the highest efficiency achieved at a contact time of 6 hours. Temperature (28-28.5°C) and pH (7.2-7.9) remained stable throughout the treatment process, supporting the performance of microorganisms in MBBR. The novelty of this research lies in the combination of MBBR biodegradation mechanism with activated carbon adsorption, which not only improves the pollutant removal efficiency but also enables its application to small-scale health facilities such as public health center with simple design and low operational cost. Conclusion: This technology offers a practical and sustainable solution for wastewater management in primary healthcare facilities, significantly contributing to developing environmentally friendly technologies and supporting policy-making related to wastewater management in Indonesia.